Sin^4(x)-cos^4(x)-sin^2(x)+cos^2(x)

Zombie1466 Zombie1466    2   24.06.2019 00:30    0

Ответы
vlad2411 vlad2411  02.10.2020 09:45
    sin^4x - cos^4x - sin^2x + cos^2x = 
= (sin^2x)^2 - (cos^2x)^2 - (sin^2x - cos^2x) = 
= (sin^2x - cos^2x) * (sin^2x + cos^2x) - (sin^2x - cos^2x) = 
Вспомним, sin^2x + cos^2x = 1 ==> 
= (sin^2x - cos^2x) * 1  - (sin^2x - cos^2x) = 
= sin^2x - cos^2x - sin^2x + cos^2x = 
=  0 

Примечание
sin^2x и  - sin^2x, а также cos^2x и - cos^2x взаимно уничтожились 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра